System to Design a Baseless and Wireless Mouse using Different Sensors (International Journal of Food and Nutritional Sciences, 2022)
It is possible to utilize hand gestures for nonverbal communication in multiple fields, including but not limited to communication for deaf-mute individuals, robot control, human-computer interaction (HCI), home automation, and medical applications. The design and development of a baseless, wireless mouse employing several sensors is the subject of this essay. This paper also describes the implementation of establishing a connection between various sensors using ESP32 microcontroller. This microcontroller also used to interact between the system and device using inbuilt Bluetooth module in ESP32. This article also describes understanding of various technologies and modules which are used in the design and development of the mouse.